Abdul Hussein Chalabi his life and political role in the history of Iraq 1876-1939 (Journal of the College of Basic Education, 2019)
The study of historical figures is one of the main axes of historical study. According to the "History from Above" approach, personalities are the makers of the historical event. As a result, the royal era witnessed many personalities who have had an impact on its political, social and economic events. Education is no exception. The post of Minister of Education has been entrusted to individuals with different social and cultural backgrounds and had an impact on the educational process of Iraq, Therefore, "Abdul Hussein Chalabi" was chosen to provide a model illustrating the nature of the this process.The research included an introduction, two axes and a conclusion as well as a list of sources, the first topic was entitled the first phase of " The life of Abdul Hussein Chalabi 1876-1921" and the second was devoted to the study "The political role of Chalabi 1922-1939" to highlight his role in the Ministry of Education and the Ministry of Works and Transportation as well as his role in the majlis al'uma (lower council of parliament)